Vocational training research on the basis of enterprise surveys : an international perspective - Bellmann, Lutz [Verfasser]; Descy, Pascaline [Herausgeber]; Tessaring, Manfred [Herausgeber] (My University, 2001)
"Reliable information on trends in labour market demand and enterprises' skills requirements is increasingly of interest not only to those researching the labour market and occupations but also to the labour market players themselves. However, as yet only inadequate information on establishments and enterprises is available. One result of this is that research activities are concentrating on the supply side of the labour market. The presentation of empirical studies based on establishment and enterprise data demonstrates the potential that research of this kind offer for vocational training research. This report therefore covers the skills requirements arising in the context of enterprises'increasing flexibility, in-company vocational training and the employment of trainees on completion of their training, and the trends discernible in the field of continuing in-company training. In this context, matched employer-employee data records are also discussed. With data records of this kind, it will in future be possible to analyse labour market domand and supply jointly. The advantages, but also the disadvantages, of longitudinal surveys as opposed to cross-sectional surveys are also brought out. The advantages of longitudinal surveys lie in the survey, i.e. the fieldwork, the sampling and the questionnaire design. Longitudinal analysis, as opposed to cross-sectional analysis, offers other advantages in the shape of the allowances made for the heterogeneity of individual businesses, and consideration of the links between cause and effect and of processes of adjustment. Certain question can be analysed only by means of panel data. The increased significance of measurement errors and selectivity problems can be regarded as a disadvantage of longitudinal data, including the panel mortality caused by various factors. As a rule, the collection of longitudinal data is considerably more costly and time-consuming, and it also takes a few years before evaluations of them can be presented." (author's abstract, IAB-Doku) ((en))
Keywords: T 1 Forschungsrichtungen; T 3 Forschungsmethoden; G 2.3.1 Arbeitsteilung & -organisation; G 1.3.3.3 Mobilität; T 3.5 Statistik; G 1.1 Soziostrukturelle & Ökonomische Entwicklungen; Berufsausbildung; Forschung; Berufliche Flexibilität; Datengewinnung; Datenanalyse; Längsschnittuntersuchung; Panel